Compartmentalized self-replication under fast PCR cycling conditions yields Taq DNA polymerase mutants with increased DNA-binding affinity and blood resistance - Arezi, Bahram; McKinney, Nancy; Hansen, Connie; Cayouette, Michelle; Fox, Jeffrey; Chen, Keith; Lapira, Jennifer; Hamilton, Sarah; Hogrefe, Holly (Frontiers in Microbiology, 2014)
Faster-cycling PCR formulations, protocols, and instruments have been developed to address the need for increased throughput and shorter turn-around times for PCR-based assays. Although run times can be cut by up to 50%, shorter cycle times have been correlated with lower detection sensitivity and increased variability. To address these concerns, we applied Compartmentalized Self Replication (CSR) to evolve faster-cycling mutants of Taq DNA polymerase. After five rounds of selection using progressively shorter PCR extension times, individual mutations identified in the fastest-cycling clones were randomly combined using ligation-based multi-site mutagenesis. The best-performing combinatorial mutants exhibit 35- to 90-fold higher affinity (lower Kd ) for primed template and a moderate (2-fold) increase in extension rate compared to wild-type Taq. Further characterization revealed that CSR-selected mutations provide increased resistance to inhibitors, and most notably, enable direct amplification from up to 65% whole blood. We discuss the contribution of individual mutations to fast-cycling and blood-resistant phenotypes.